2019
DOI: 10.1111/eea.12762
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐induced plants do not affect oviposition but do affect fitness of subsequent herbivores on canola

Abstract: The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is oligophagous on plants in the Brassicaceae, and is considered one of the most significant insect pests of canola (Brassica napus L.), a major oilseed crop grown in the Prairie Provinces of Canada. The bertha armyworm (BAW), Mamestra configurata Walker (Lepidoptera: Noctuidae), is a generalist herbivore that preferentially feeds on canola plants. In the canola growing season in the Prairie Provinces of Canada, DBM feeding occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Herbivore feeding behavior is an important determinant of herbivore adaptive response to plant defenses (Karban, 2011;Weeraddana & Evenden, 2019). Yet, in our case, larvae were not allowed to move freely and leave the potted tree to find a more suitable host, or more generally escape competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbivore feeding behavior is an important determinant of herbivore adaptive response to plant defenses (Karban, 2011;Weeraddana & Evenden, 2019). Yet, in our case, larvae were not allowed to move freely and leave the potted tree to find a more suitable host, or more generally escape competition.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors reported a mismatch between prior herbivory effects on female oviposition preference vs larval growth, consumption or survival of their offspring (Godinho et al, 2020; Wise & Weinberg, 2002; Bergamini & Almeida-Neto, 2015; Martinez et al, 2017). For instance, Weeraddana and Evenden (2019) found that herbivory by the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae) on canola plants ( Brassica napus L.) had no effect on subsequent oviposition by the bertha armyworm, Mamestra configurata Walker (Lepidoptera: Noctuidae) whereas its larvae had reduced growth on previously damaged plants. Thus, in order to quantify the effect of prior herbivory on subsequent herbivore performance, we need to assess how it affects both female choice and progeny performance in attacked and non-attacked hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous herbivory can also affect the oviposition preference of herbivores that arrive later. Several studies have demonstrated that mated females can discriminate between host plants that have been previously attacked by insect herbivores (Wise & Weinberg, 2002;Stam et al, 2014;Moura et al, 2017;Barnes & Murphy, 2018;Moreira et al, 2018;Weeraddana & Evenden, 2019), thereby reducing competition between herbivores separated in time. Mated females can directly detect the present, past and possibly future presence of competitors themselves.…”
Section: Introductionmentioning
confidence: 99%
“…However, several authors reported a mismatch between prior herbivory effects on female oviposition preference vs larval growth, consumption or survival of their offspring (Wise & Weinberg, 2002;Bergamini & Almeida-Neto, 2015;Martinez et al, 2017;Godinho et al, 2020). For instance, Weeraddana and Evenden (2019) found that herbivory by the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae) on canola plants (Brassica napus L.) had no effect on subsequent oviposition by the bertha armyworm, Mamestra configurata Walker (Lepidoptera: Noctuidae) whereas its larvae had reduced growth on previously damaged plants. Thus, in order to quantify the effect of prior herbivory on subsequent herbivore performance, we need to assess how it affects both female choice and progeny performance in attacked and non-attacked hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the study found that long‐distance cues were more influential than short‐distance cues, the authors clearly identify a synergy between the two cue types. Weeraddana & Evenden () describe how feeding‐induced defenses by a specialist herbivore, diamondback moth, Plutella xylostella L. (Lepidopera: Plutellidae), in canola deterred subsequent herbivory by a generalist herbivore, bertha armyworm, Mamestra configurata Walker (Lepidoptera: Noctuidae), and negatively impacted its fitness. Mechanical damage simulating the specialist feeding, on the other hand, did not affect the generalist feeding and fitness.…”
mentioning
confidence: 99%